BAHASA GAMBAR (ICONOGRAPHY): BAHASA PURBA UNTUK KOMUNIKASI MASYARAKAT MODERN - Prasetya, Hendri (Universitas Prof. Dr. Moestopo (Beragama), 2006)
Long beforeÂ the invention of alphabetical code in Â human language system, primitive Â communities Â uses Â a Â picture Â or Â sign Â asÂ a Â medium Â to interpret, memorized Â and transmitted Â theirÂ daily Â life Â reality. They drew a picture of an object around them in a cave, stone or wood. Its Â the only communication system they have to express their life experience.Since the alphabetical system found in human civization, this picture language slowly fade. Iconography becomes a second language that use only by a specific group for a special contex. But this time, iconography becomes an alternative language that use in large contex of modern lifes. One of the most phenomenal systems of picture language in modern life was developed by Microsoft Windows called HUIâs (Graphical User Interface).